Corrosion and Wear Properties of Nanoclay- polyester Nanocomposite Coatings Fabricated by Electrostatic Method. (2015) - Golgoon, A.; Aliofkhazraei, M.; Toorani, M.; Moradi, M.H.; Rouhaghdam, A. Sabour
Abstract: In this paper, polyester coating as the matrix was combined with 5wt% of clay nanoparticle and nanocomposites coating was applied on the surface of plain carbon steel components by electrostatic device. Coating structure and morphology of nanoparticles were investigated by SEM and TEM. The effect of adding nanoparticles and curing type on the corrosion resistance properties of coatings were investigated by Tafel test. The results of Tafel test shows that coating corrosion resistance is increased highly by adding nanoclay. Furthermore coatings cured in oven show higher corrosion resistance than coatings cured in microwave. The results of wear test show that adding nanoparticles markedly increases wear resistance of nanocomposite coating also, the type of curing affects on this properties.